March 23, 2017

Post a New Question

Posted by on Tuesday, November 27, 2012 at 11:57pm.

write the expression as a single logarithm


Please show work

  • college algebra - , Friday, November 30, 2012 at 5:06am

    Basic rules: lna+lnb=ln(ab) and lna-lnb=ln(a/b) also lna^x=xlna

    ln[x/(x-2)*(x+2/x)]-ln(x^2-4)= ln[(x^2+2)/(x-2)]-ln(x^2-4)= ln [divide]hence simplify fraction and get answer

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question